2020
DOI: 10.1111/cei.13531
|View full text |Cite
|
Sign up to set email alerts
|

Different subsets of haematopoietic cells and immune cells in bone marrow between young and older donors

Abstract: The differences in the frequency and immune differentiation potential of HSCs in BM between young donors and older donors may partly explain the different outcomes of allo‐HSCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…Some studies have shown that the adaptive immune system, especially T cells, is more susceptible to ageing than the innate immune system [3,4]. Our and other previous studies showed decreased frequencies of bone marrow (BM) lymphoid progenitor cells and naïve T cells but increased frequencies of memory T cells, as well as unbalanced effector T cell subset differentiation, such as increased T helper (Th)-1 and T cytotoxic (Tc)-1 cells, in elderly individuals [1,2,5]. Emerging evidence has indicated that decreased BM lymphoid progenitor cells and involution of the thymus may be responsible for the alterations in T cell subsets with ageing [6][7][8].…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…Some studies have shown that the adaptive immune system, especially T cells, is more susceptible to ageing than the innate immune system [3,4]. Our and other previous studies showed decreased frequencies of bone marrow (BM) lymphoid progenitor cells and naïve T cells but increased frequencies of memory T cells, as well as unbalanced effector T cell subset differentiation, such as increased T helper (Th)-1 and T cytotoxic (Tc)-1 cells, in elderly individuals [1,2,5]. Emerging evidence has indicated that decreased BM lymphoid progenitor cells and involution of the thymus may be responsible for the alterations in T cell subsets with ageing [6][7][8].…”
Section: Introductionmentioning
confidence: 59%
“…Numerous studies have shown that the occurrence of aGVHD was related to increased frequencies of donor Th1 and Tc1 cells and reduced frequencies of Th2 and Tc2 cells [37,38,41]. Furthermore, we recently reported that young donors had lower percentages of Th1 and Tc1 cells than old donors [5], which could partly explain why patients receiving transplants from young donors showed less aGVHD than those who received transplants from old donors [42,43]. However, the in-depth reason why the aGVHD incidence was affected by donor age remains to be explored.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…Some studies have shown that the adaptive immune system, especially T cells, is more susceptible to ageing than the innate immune system [3,4]. Our and other previous studies showed decreased frequencies of bone marrow (BM) lymphoid progenitor cells and naive T cells but increased frequencies of memory T cells, as well as unbalanced effector T cell subset differentiation, such as increased T helper type 1 (Th1) and T cytotoxic 1 (Tc1) cells, in elderly individuals [1,2,5]. Emerging evidence has indicated that decreased BM lymphoid progenitor cells and involution of the thymus may be responsible for the alterations in T cell subsets with ageing [6][7][8].…”
Section: Introductionmentioning
confidence: 61%
“…After 3 days of co-culture, CD3 + T cells were treated with cell stimulation cocktail (×500; eBioscience, San Diego, California, USA), as the manufacturer's instructions, to induce CD3 + T cells activation and cytokine secretion. Then, we evaluated the IL-4, IFN-γ, IL-17 and forkhead box protein 3 (FoxP3) levels by flow cytometry using the following monoclonal antibody panel: CD3-APC-H7, CD8-V500, CD25-PE/Cy7, IL-4-PE, IFN-γ-peridinin chlorophyll cyanin 5.5 (PerCPCy5.5), IL-17-FITC and FoxP3-APC (BD Biosciences) [5,[28][29][30]. The immunophenotyping of T cell subsets, including Th1, Th2, Th17, Tc1, Tc2 and regulatory T cells (Tregs), were in keeping with our previous studies [5,[28][29][30][31].…”
Section: Immunophenotype Analysis Of the Cocultured T Cell Subsetsmentioning
confidence: 99%